Criminological Juridical Analaysis of The Crime of Premeditated Murder of a Beautiful Model in Pandeglang District - Dewi Fadhia Gayatri gayatri; Hasuri (Journal Equity of Law and Governance, 2024)
This research aims to find out what factors make the perpetrators of murder commit these acts seen from the theory of criminology. In this research the author uses the Empirical Normative Legal Research methodology. This empirical normative legal research method is basically a combination of normative legal approaches by adding various empirical elements. To collect data in this study, researchers used secondary data, namely data obtained from literature. The usefulness of secondary data is to find initial data or information, obtain a theoretical basis or legal basis, obtain limitations, definitions, meaning of a term. Judging from the theory of criminology, the perpetrators of the crime of murder are motivated by two factors, namely revenge factors (heartache) and social environmental factors. The perpetrator is subject to Article 340 of the Criminal Code "whoever intentionally and with premeditation takes the life of another person, shall be punished by death or life imprisonment or a maximum imprisonment of twenty years." in the Decision of the Supreme Court of the Republic of Indonesia Number. 126/Pid.B/2023/PN Pdl the perpetrator was sentenced to 15 years imprisonment. On the other hand, Criminal Law tends to only pay attention to how to provide punishment and deterrent effects to the perpetrator, without paying attention to why the perpetrator committed the act. This disregard for the rights of victims often creates its own problems. However, the study of criminology can provide a deeper understanding of the causes of crime, including premeditated murder.